Cytokine profiles in patients with newly diagnosed multiple myeloma: Survival is associated with IL-6 and IL-17A levels. (February 2021) - Gu, Jiayan; Huang, Xin; Zhang, Yi; Bao, Chenhui; Zhou, Ziyang; Jin, Jie
Highlights: IL-6 and IL-17A are correlated with poor overall survival of MM patients. IL-6 and IL-17A are also correlated with poor progression-free survival. Cytokine deregulation is a powerful predictor of the clinical prognosis in MM. Abstract: Background: Identifying specific risk factors associated with multiple myeloma (MM) remains a significant issue. Different cytokines take part in the pathogenesis, progression, and prognosis of MM. Therefore, this study aimed to investigate the correlations between serum cytokine levels and clinical characteristics and determine their effects on disease progression and survival of MM patients. Methods: We retrospectively analyzed the serum levels of 7 cytokines in 105 patients with newly diagnosed MM and in 20 healthy subjects. Interleukin (IL)-2, IL-4, IL-6, IL-10, and IL-17A, tumor necrosis factor (TNF)-α, and interferon (IFN)-γ were quantitatively determined by cytometric bead assay techniques. The concentrations of each cytokine were compared between the MM patients and healthy subjects using the Mann–Whitney U test. The Kaplan–Meier method was used to analyze progression-free survival (PFS) and overall survival (OS). Results: Serum IL-2, IL-4, IL-6, IL-10, IL-17A, TNF-α, and IFN-γ levels were higher in patients with newly diagnosed MM than in healthy controls. Positively significant correlations were found between IL-6, IL-10, IL-17A, and β2-microglobulin. Significant correlations were also observed between IL-6 and IL-10, and lactate dehydrogenase. The overall response rate of low-IL-6 and IL-17A patients was significantly higher than that of high-IL-10 and IL-17A patients (P < 0.01). Univariate and multivariate analyses revealed that serum IL-6 levels were >3 pg/mL, serum IL-17A levels were >4 pg/mL, and treatment regimens were independent prognostic factors for PFS and OS. Conclusions: Cytokine deregulation, especially that of IL-6 and IL-17A, may be a powerful predictor of clinical prognosis for MM patients.